Transparansi dan Ketepatan Sasaran Dalam Penyaluran Program Indonesia Pintar: Studi Kasus Sekolah Dasar di Kecamatan Kuta Utara - Wahyuni, Made Dwi Tyasari; Prabawati, I Putu Anik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the transparency and targeting in the implementation of the Smart Indonesia Program (PIP) at the primary school level in Kuta North District. Using a qualitative descriptive method, this study found that the channeling of PIP assistance still faces various challenges, such as inconsistencies in recipient data between Dapodik and DTKS, weak updating of data, as well as a lack of transparency of information in schools. Although PIP has contributed in suppressing dropout rates, its effectiveness has not been optimal due to weak interagency synergies and minimal public participation in supervision. Therefore, improvement of data systems and increased capacity of program managers are important steps to improve the quality of PIP implementation in Kuta North District.